DASAR TEOLOGIS PENDIDIKAN ISLAM MULTIKULTURAL - Moh Masduki; Nurul Malikah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2021)
Abstract: Multicultural education paradigm is important to develop with the facts and realities of the pluralistic and diverse Indonesian nation. Because Islam is also part of this diversity, multicultural Islamic education is automatically also the responsibility of Indonesian Muslims to develop. The studies explored in this research are focused on examining the theological basics of multicultural Islamic education including the verses of the Koran which are the basis for developing a multicultural Islamic education paradigm.This study is a literature review by looking for and digging up written data related to the focus of the study, these texts will be studied in such a way by looking at several angles of reading them and then drawing a red thread which is then used as the final goal in this study. From the results of this discussion, it can be concluded that multicultural Islamic education is important to be developed in a plural and multicultural area, multicultural Islamic education must be able to develop universal principles in order to foster personalities who can become peacemakers in that plural environment. From this study it is also found that theologically normative Islam has foundations and principles as the foundation for developing multiculural Islamic education, these principles are equality or al-musawah, compassion or ar-rahmah, justice or al-'adl, tolerance or al-tasamuh, togetherness or at-ta'aruf.